ANTAGONISTIC BACTERIA AND THEIR POST-CULTURE LIQUIDS IN THE PROTECTION OF PEA (Pisum sativum L.) FROM DISEASES - Danuta Pięta; Alina Pastucha (Acta Scientiarum Polonorum: Hortorum Cultus, 2008)
The purpose of the paper was to establish the protective effect of the microbiological material prepared from the cells of Bacillus sp. Bk 30 and Pseudomonas sp. Pk 28 and their post-culture liquids against soil-borne pathogenic fungi. The use of biological control improved the emergences, healthiness of pea plants and their yielding. Despite using the microbiological material for seed dressing, pea plants were infected by Altenaria alternata, Ascochyta pisi, Botrytis cinerea, Fusarium culmorum, Fusarium oxysporum f. sp. pisi, Fusarium solani, Phoma exigua, Pythium irregulare, Rhizoctonia solani and Sclerotinia sclerotiorum. Among the applied microbiological material, the best protective effect against plant pathogens was observed for bacterium Bacillus sp. Bk 30 and its postculture liquid.